Analysis of physical activity in psoriatic arthritis: relationship with clinical and analytical parameters and comorbidity—description of the sedentary patient - Toledano, Esther; Chacón, Carolina Cristina; Compán, Olga; Gómez-Lechón, Luis; Hidalgo, Cristina; Ibañez, Marta; Márquez, Antonio; Montilla, Carlos (Frontiers in Medicine, 2024)
Objective: To relate physical activity and sedentary lifestyle to clinical, biological, functional and comorbid parameters in a cohort of patients with psoriatic arthritis (PsA).Methods: Cross-sectional study including 232 patients diagnosed with PsA. Physical activity and sedentary lifestyle were obtained using the IPAQ questionnaire. Demographic, clinical and biological variables measured were age, time since PsA diagnosis, smoking, type of treatment used, clinical form, presence of enthesitis, dactylitis (present or past), fatigue, TNF-alpha and IL-6. Activity and functionality were measured by DAPSA and HAQ in peripheral forms and ASDAS-PCR and BASFI in axial forms. Disease impact was assessed by PSAID. Alongside comorbidities, obesity, anxiety, depression (HADS) and sleep quality (ISI) were assessed.Results: The mean age was 54.6 (SD: 11.4) years, 54.3% being male. 25.6% of patients were sedentary. Physical activity and sedentary lifestyle were inversely correlated with fatigue, activity, functionality and disease impact. Within comorbidities, they correlated with anxiety, depression and insomnia. In addition, physical activity was inversely correlated with obesity. In linear regression analysis, physical activity was related to BMI; ß: -0.1; p<0.04; (95%CI: -194.1–4.5), R 2 : =0.11. In logistic regression analysis, sedentary lifestyle was related to pain; OR: 1.5; p<0.001 (95%CI:1.1-1.8), R 2 Nagelkerke:0.36.Conclusions: A quarter of the patients were sedentary. Lack of physical activity correlated with worse parameters of clinical activity, functionality, disease impact and presence of comorbidities.